DESA KASANG KUMPEH 2006 – 2024 - Andreza Tri Nugraha; Ulul Azmi (Universitas Batanghari Jambi, 2026)
This study examines the development process of Kasang Kumpeh Village since it was officially established as a definitive village in 2006 until 2024, as well as its impact on the lives of the residents. This research uses historical research methods with stages of heuristics, source criticism, interpretation, and historiography. The research sources consist of primary sources in the form of interviews with village officials, community leaders, and residents of Kasang Kumpeh Village, as well as secondary sources in the form of village archives, official documents, and relevant literature. A multidisciplinary approach is used to analyze the village's development comprehensively by utilizing concepts from history, sociology, cultural anthropology, economics, and politics. The results of the study show that the development of Kasang Kumpeh Village is influenced by several main factors, namely the potential of natural resources, the quality of human resources, and a strategic geographical location. This development is reflected in the increased construction of village infrastructure, such as roads, village offices, educational facilities, places of worship, as well as the entry of new economic activities through the establishment of several companies and shops. These changes encourage a shift in the livelihoods of the population from the agricultural sector to the trade, service, and company labor sectors.